2011
DOI: 10.3390/en4030532
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Optimization for Hybrid Electric Vehicle Parameters Based on Multi-Objective Genetic Algorithms

Abstract: Compared to conventional vehicles Hybrid Electric Vehicles (HEVs) provide fairly high fuel economy with lower emissions. To enhance HEV performance in terms of fuel economy and emissions, and ensure user satisfaction with driving performance, the need for simultaneous optimization for the main parameters of powertrain components and control system is inevitable. However, this problem is challenging due to the large amount of coupling design parameters, conflicting design objectives and nonlinear constraints. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 22 publications
0
41
0
Order By: Relevance
“…It was found that the promotion of PHEVs and EVs could help cut per-kilometer petroleum use to a great extent; however, it makes the CO 2 emission mitigation becomes even more difficult to achieve. The evaluation of HEVs emissions were also studied in [17].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the promotion of PHEVs and EVs could help cut per-kilometer petroleum use to a great extent; however, it makes the CO 2 emission mitigation becomes even more difficult to achieve. The evaluation of HEVs emissions were also studied in [17].…”
Section: Introductionmentioning
confidence: 99%
“…The methods based on Calculus of Variations obtain a local optimization result, for example, Pontryagin's minimum principle. Other examples of optimization can be found in [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…This is not only related to the design parameters of the power system, but also the control parameters of the energy management strategy (EMS). To improve HEV performance in terms of fuel economy and ensure excellent driving performance, the simultaneous optimization for the main parameters of powertrain components and control system is necessary [1]. Recently, numerous works have been proposed to find the best solution.…”
Section: Introductionmentioning
confidence: 99%